Measurable residual disease, FLT3‐ITD mutation, and disease status have independent prognostic influence on outcome of allogeneic stem cell transplantation in NPM1‐mutated acute myeloid leukemia. (20th January 2022) - Al Hamed, Rama; Labopin, Myriam; Daguindau, Etienne; Niittyvuopio, Riitta; Huynh, Anne; Socié, Gerard; Srour, Micha; Henri Bourhis, Jean; Kröger, Nicolaus; Tholouli, Eleni; Choi, Goda; Poiré, Xavier; et al.
Abstract: Nucleophosmin ‐ 1 ( NPM1 ) mutations in acute myeloid leukemia (AML) confer a survival advantage in the absence of FLT3 ‐internal tandem duplication ( FLT3 ‐ITD). Here, we investigated the main predictors of outcome after allogeneic hematopoietic stem cell transplantation (allo‐HCT). We identified 1572 adult (age ≥ 18 year) patients with NPM1 ‐mutated AML in first complete remission (CR1:78%) or second complete remission (CR2:22%) who were transplanted from matched sibling donors (30.8%) or unrelated donors (57.4%) between 2007 and 2019 at EBMT participating centers. Median follow‐up for survivors was 23.7 months. FLT3 ‐ITD was present in 69.3% of patients and 39.2% had detectable minimal/measurable residual disease (MRD) at transplant. In multivariate analysis, relapse incidence (RI) and leukemia‐free survival (LFS) were negatively affected by concomitant FLT3 ‐ITD mutation (HR 1.66 p  = 0.0001, and HR 1.53, p  < 0.0001, respectively), MRD positivity at transplant (HR 2.18, p  < 10 −5 and HR 1.71, p  < 10 −5, respectively), and transplant in CR2 (HR 1.36, p  = 0.026, and HR 1.26, p  = 0.033, respectively), but positively affected by Karnofsky score ≥90 (HR 0.74, p  = 0.012, and HR 0.7, p  = 0.0002, respectively). Overall survival (OS) was also negatively influenced by concomitant FLT3 ‐ITD (HR 1.6, p  = 0.0001), MRD positivity at transplant (HR 1.61, p  < 10 −5 ), and older age (HR 1.22 per 10 years, p  < 0.0001), but positively affected by matched sibling donor (unrelated donor: HR 1.35, p  = 0.012; haploidentical donor: HR 1.45, p  = 0.037) and Karnofsky score ≥90 (HR 0.73, p  = 0.004). These results highlight the independent and significant role of FLT3 ‐ITD, MRD status, and disease status on posttransplant outcomes in patients with NPM1 ‐mutated AML allowing physicians to identify patients at risk of relapse who may benefit from posttransplant prophylactic interventions. Abstract : Acute myeloid leukemia (AML) is a heterogenous disease with a highly variable prognosis and high overall mortality whereby the management is influenced by patient characteristics and biological, genetic, and molecular characteristics of the disease. The impact of minimal residual disease (MRD), NPM‐1 mutation status, FLT3‐ITD mutation status, and disease status at transplant has been individually investigated. This study examines the aggregate influence of those factors on outcome post‐transplant in NPM1‐mutated AML.